The BMI Paradox and Robotic Assisted Partial Nephrectomy - Kott, Ohad; Golijanin, Borivoj; Pereira, Jorge F.; Chambers, Alison; Knasin, Alison; Tucci, Christopher; Golijanin, Dragan (Frontiers in Surgery, 2020)
Introduction: Partial nephrectomy (PN), has become the gold standard for the surgical management of small renal masses, due to excellent oncologic control with concomitant preservation of nephron units. However, data regarding the association of obesity with perioperative outcomes following PN are mixed. Therefore, the association between obesity (using BMI) and post-operative complications (POC) rate following Robotic assisted laparoscopic PN (RPNx) was tested. Methods: Two hundred and fifty-one adult patients who underwent RPNx from 1/2011 to 5/2017 at a single institution, with at least 90 days follow-up were identified and included. No patients were excluded. Electronic medical records were reviewed to record all POC within 90 days of surgery. A piecewise generalized linear model for binary outcomes (logistic) was used to model the proportion of subjects with POC by their BMI. The slope of the line is adjusted to a BMI of 30 Kg/m2. Results: BMI is significantly associated with POC rate. POC rate decreased with increasing BMI below the inflection point of 30 Kg/m2 (0.848[0.756, 0.952]) (OR [95% CI], p = 0.005). POC rate was found to increase with increasing BMI above the BMI inflection of 30 Kg/m2 (1.102 [1.027, 1.182], p = 0.0071). Conclusions: In this cohort study, BMI showed an association with PC. It may be important to take BMI into account in surgical and clinical management considerations of RPNx, since higher rates of POC are associated with patients who are underweight, morbidly obese, and even with normal BMI. Further research is required on larger cohorts of RPNx patients to provide better description of this phenomenon and elucidate the role of BMI in development of POC.